IMPACT OF DEVELOPMENT EXCHANGE CENTRE (DEC) MICROCREDIT PROGRAMME ON CROP OUTPUT AND STANDARD OF LIVING AMONG WOMEN FARMERS IN KADUNA STATE, NIGERIA - Adamu, B. D.; Michael , H. Y. (FUDMA JOURNAL OF SCIENCES, 2021)
This study examined the impact of Development Exchange Centre microcredit programme on crops output and standard of living among women farmers in Kaduna State, Nigeria. A multi-stage sampling method was employed to select 420 respondents. Primary data were collected through the use of questionnaires and were subjected to both descriptive and inferential statistics. The mean farming experience was 22 years for DEC participants and 19 years for non-DEC participants while mean farm size for participants and non-DEC participants was 2.0 ha. Determinant of standard of living on programme participants, the study concludes that, age (0.0405, P
Keywords: Impact, DEC, Crops output, Poverty Standard of living, Women farmers